PENERAPAN METODE PEMBELAJARAN GROUP INVESTIGATION BERBANTUAN MEDIA FLANELGRAF UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA (Studi Kelas IV SDN Jetak 01, Kecamatan Getasan, Kabupaten Semarang) - Widyanto, Prasetyo (Universitas Nusantara PGRI Kediri, 2017)
The purpose of this research is to increase the interest and the students' learning outcomes of science subjects class IV SDN Jetak 01 District Getasan, Semarang regency. The subjects of this study were 26 students of class IV. This type of research is a classroom action research (CAR). Data collection techniques used observation, test, and student response questionnaires. The results showed that learning using group investigation method assisted flanelgraf media can increase interest and student learning outcomes. The percentage of students' interest in learning reaches 97% in cycle one. There is an increase in learning outcomes, where the average pre cycle value is 71 and cycle one becomes 81. Keywords: group investigation, flanelgraf, students’ interest, students’ learning outcome, science